In situ formation of catalytically active graphene in ethylene photo-epoxidation - Xueqiang Zhang (Nature Portfolio, 2018)
In situ studies under working conditions are important in atomic-level elucidation, design, and optimization of industrially relevant catalysts. Here, the authors report an in situ study of an Ag ethylene photo-epoxidation catalyst using surface enhanced Raman scattering, which uncovers an unconventional mechanism.